Theoretical Views on the Depoliticization and the Twilight of the Political - Birešev, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2024)
The paper examines two different conceptual perspectives on how politics and political have changed at the end of the 20th and the beginning of the 21st century, as well as the specific understandings of depoliticization implied in these perspectives. The first part of the paper discusses theories (Rancière, Mouffe, and Žižek) that consider depoliticization as a result of the systematic foreclosure or repudiation of the political (i.e. moments of antagonism) and the post-political/post-democratic condition. The second part of the paper focuses on approaches (Flinders and Buller, Flinders and Wood, Crouch, and Hay) that see depoliticization as a specific (neoliberal) governing strategy or technique. These approaches look at how politicians position themselves as agents of their own disempowerment and shift the responsibility for public policy away from the state through institutional, legislative, and ideological-rhetorical strategies. The paper also examines the role of anti-politics and the technocratic principle of governance in the erosion of the political and the growing political disaffection. The article concludes by discussing the strengths and limitations of the presented theoretical approaches to depoliticization.